Diskursus Keabsahan Al-Qiraat Al-‘Ashr sebagai Bacaan Mutawatir - Muzammil, Iffah (Department of Qur'an dan Hadith Faculty of Ushuluddin and Philosophy UIN Sunan Ampel Surabaya, 2015)
Ten qirâ’ah belongs to the ten Imams of Qur’anic recitaters. It composes seven Imams who are remarkably recognized in Muslim traditions mainly introduced by Ibn Mujâhid (245- 324 H), with three additional Imams, Abû Ja‘far al-Qa‘qâ‘, Abû Ya‘qûb al-Ha?ramî, and Khalaf bin Hishâm. Different from seven qirâ’ah that is officially approved (mutawâtir) by most of Muslim scholars, the existence of ten qirâ’ah is still debatable. Indeed, some of scholars classify it as poor qirâ’ah (shâdh). Five centuries later after Ibn Mujâhid’s introduction on seven qirâ’ah, al-Jazarî (d. 833 H) argues some evidences on the validity of chain transmission (sanad) of the last three Imams. In the hand of al-Jazarî, the ten qirâ’ah is attested to be completely meeting a requirements of qirâ’ah such like, reliable chain’s transmission, compatible to rasm ‘Uthmânî, and convenient to Arabic rules. Therefore, there is no reason to leave and refuse the last three Imams (ten qirâ’ah) in the Islamic tradition of Qur’anic recitation.